Binisaya, a new generation of Cebuano filmmakers an interview with Keith Deligero and Ara Chawdhury - Campos, Patrick F. (2017)
Access online through this link: http://plarideljournal.org/article/binisaya-new-generation-cebuano-filmmakers-interview-keith-deligero-ara-chawdhury
Keywords: Filmmakers; Deligero, Keith -- Interviews; Chawdhury, Ara -- Interviews; Motion pictures -- Cebu